An in vitro study on the antibacterial potential of some edible Philippine seaweeds against streptococcus mutans - Cruzat, Rosabelle C.
Bacteriologic studies have been made several years ago to evaluate the role of various microorganisms in the etiology of dental caries. In the study made by Keyes and Fitzgerald in 1960, it has been recognized that Streptococcus mutans is a very efficient microorganism which attacks the calcified structures of the teeth, contributing to the formation of dental caries. It has also been found that fluoride protects the teeth from the cariogenic process. Furthermore, in a study conducted by Chua and Chung in 1986, some edible, locally available, seaweeds contain fluoride. Using an in vitro experiment, this study investigated on the antibacterial potential of three edible seaweeds, which are widely available in the Philippines, against Streptococcus mutans. Extracts were collected from Gelidiella acerosa, Sargassum spp. and Kappaphycus alvarezii, using the solvent combination 1:1 methanol:chloroform. After collection of extracts, the alcoholic solvents were allowed to evaporate with the use of a rotary evaporator, and the crude seaweed extracts were reconstituted in ethanolic water and 9.09%, 23.07%, and 37.50% extract concentrations were obtained from them. These were later tested for antibacterial activity against Streptococcus mutans, using the Cylinder Assay Method. The extracting solvent methanol:chloroform and the diluent ethanolic water were also tested for antibacterial activity. Positive control used was Chlorhexidine. Results revealed that the crude extracts of the seaweeds Gelidiella acerosa, Kappaphycus alvarezii, and Sargassum spp. possess an antibacterial property against Streptococcus mutans. Their antibacterial activity is greater than the antibacterial activity of Chlorhexidine. Among the three seaweeds, the highest antibacterial activity is manifested by the extract of Sargassum spp. and the least is exhibited by Kappaphycus alvarezii; however, a small difference between the antibacterial properties of Gelidiella acerosa and Kappaphycus alvarezii is present. Lastly, it has been found that there is no significance on the concentration of seaweed extract on the strength of antibacterial activity exhibited against Streptococcus mutans. The results provide further evidence that crude extracts from the seaweeds Gelidiella acerosa, Kappaphycus alvarezii, and Sargassum spp. are capable of inhibiting the growth of Streptococcus mutans, regardless of the concentration of the extract.